2014
DOI: 10.1007/s40258-014-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

EXOGEN Ultrasound Bone Healing System for Long Bone Fractures with Non-Union or Delayed Healing: A NICE Medical Technology Guidance

Abstract: A routine part of the process for developing National Institute for Health and Care Excellence (NICE) medical technologies guidance is a submission of clinical and economic evidence by the technology manufacturer. The Birmingham and Brunel Consortium External Assessment Centre (EAC; a consortium of the University of Birmingham and Brunel University) independently appraised the submission on the EXOGEN bone healing system for long bone fractures with non-union or delayed healing. This article is an overview of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…This is a complex question, but the simplest answer is that there are no RCTs that directly compare LIPUS to modern surgical techniques for nonunion [35]. In the absence of such trials, clinicians should be reluctant to recommend LIPUS over the proven benefits of nonunion surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a complex question, but the simplest answer is that there are no RCTs that directly compare LIPUS to modern surgical techniques for nonunion [35]. In the absence of such trials, clinicians should be reluctant to recommend LIPUS over the proven benefits of nonunion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of such trials, clinicians should be reluctant to recommend LIPUS over the proven benefits of nonunion surgery. However, the National Institute for Health and Care Excellence (NICE) in the United Kingdom evaluated the evidence supporting LIPUS to promote healing of fracture nonunion [35]. NICE concluded that ''clinical evidence supports the use of [LIPUS] in non-union long bone fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A), to an intensity of 30 mW/cm 2 spatial averagetemporal average (SATA), with a power of 117 mW (Harrison et al, 2016). LIPUS shows particular efficacy in treating bone nonunion fractures (Nolte et al, 2001;Rutten et al, 2007;Zura et al, 2015a), and has been approved by the US FDA for treating both fresh fractures and nonunion fractures, and by NICE in the UK for treating nonunion fractures (Higgins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%